Pengaruh Motivasi Belajar Terhadap Minat Belajar Peserta Didik Kelas VI Mata Pelajaran Agama Islam di Sekolah Dasar Negeri 14 Sendoyan Bungor Kecamatan Sejangkung Kabupaten Sambas - Yuni Asti (Jurnal Pendidikan Dasar Islam, 2023)
This study aims to find out: (1) Learning Motivation in Class VI Students at Sendoyan Bungor 14 State Elementary School, Sejangkung District, Sambas Regency, 2020/2021 Academic Year. (2) Interest in learning in class VI students at Sendoyan Bungor 14 State Elementary School, Sejangkung District, Sambas Regency, for the 2020/2021 academic year. (3) The significant effect of learning motivation on learning interest of class VI students at Sendoyan Bungor 14 State Elementary School, Sejangkung District, Sambas Regency, 2020/2021 Academic Year. This research is a quantitative research with an associative approach. The subjects of this study were all grade VI students of SD Negeri 14 Sendoyan Bungor, Sejangkung District, Sambas Regency for the 2020/2021 academic year, a total of 35 students. Data collection techniques using questionnaires and documentation. Data analysis techniques used simple regression analysis to answer the first and second research and multiple regression analysis to answer the third research question. The results of this study indicate that: (1) There is a positive and significant influence on learning motivation in class VI students at SD Negeri 14 Sendoyan Bungor, Sejangkung District, Sambas Regency, for the 2020/2021 academic year of 22.4% with a significance value of 0.007 <0. 05 and Fcount of 8.388. (2) There is a positive and significant effect of interest in learning in grade VI students at SD Negeri 14 Sendoyan Bungor, Sejangkung District, Sambas Regency for the 2020/2021 academic year of 18.4% with a significance value of 0.016 <0.05 and Fcount of 6.545. (3) There is a significant influence between learning motivation on learning interest of class VI students at SD Negeri 14 Sendoyan Bungor, Sejangkung District, Sambas Regency for the 2020/2021 academic year of 31% with a significance value of 0.006 <0.05 and Fcount of 6.279.